Pleistocene persistence and expansion in tarantulas on the Colorado Plateau and the effects of missing data on phylogeographical inferences from RADseq. Issue 19 (29th August 2020) - Graham, Matthew R.; Santibáñez‐López, Carlos E.; Derkarabetian, Shahan; Hendrixson, Brent E.
Abstract: Montane species endemic to the "sky islands" of the North American southwest were significantly impacted by changing climates during the Pleistocene. We combined mitochondrial and genomic data with species distribution modelling to determine whether Aphonopelma marxi, a large tarantula from the nearby Colorado Plateau, was similarly impacted by glacial climates. Genetic analyses revealed that the species comprises three main clades that diverged in the Pleistocene. A clade distributed along the Mogollon Rim appears to have persisted in place during glacial conditions, whereas the other two clades probably colonized central and northeastern portions of the species' range from refugia in canyons. Climate models support this hypothesis for the Mogollon Rim, but late glacial climate data appear too coarse to detect suitable areas in canyons. Locations of canyon refugia could not be inferred from genomic analyses due to missing data, encouraging us to explore the effect of missing loci in phylogeographical inferences using RADseq. Results from analyses with varying amounts of missing data suggest that samples with large amounts of missing data can still improve inferences, and the specific loci that are missing matters more than the number of missing loci. This study highlights the profound impact of Pleistocene climates on tarantulas endemic to the Colorado Plateau, as well as the mixed nature of the region's fauna. Some animals recently colonized from nearby deserts as glacial climates receded, whereas others, like tarantulas, appear to have persisted on the Mogollon Rim and in refugia associated with the region's famous river‐cut canyons.